FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PEMBIAYAAN SYARIAH MELALUI PROGRAM RUMAH PEMBIAYAAN PERTANIAN - Deby Diana; Tuti Karyani (Universitas Galuh Ciamis, 2021)
In Indonesia the agricultural sector is a sector that is considered to have a high enough risk, so the interest of financial institutions is less to fund this sector. An alternative that needs to be done to reach capital in the agricultural sector is by having a capital institution that is able to offer a system that is easy and not burdensome for farmers. This is implemented through the RPP program which is expected to help farmers in capital through Islamic financing. The purpose of this study is to analyze the effectiveness of Islamic financial institutions and see what are the factors that can influence the amount of sharia financing taking through the RPP program. This research design uses is quantitative with the census method. This study uses multiple linier regression analysis methods. The results showed that the factors that directly affect the amount od Islamic financing through the RPP are family dependents, length of time being customers, business experience, frequency of financing and business scale. Factors that inversely affect the amount of funding taken through the RPP are business income and years of education.